Teaching differently: a hybrid delivery model - Petrova, K. (GBATA, 2001)
A variety of frameworks for distant, online and flexible learning have been proposed. This paper looks into the defining features of some of these models and describes the hybrid model of flexible delivery. The hybrid model integrates face-to-face classes of instructed practical works, online learning environments and distance learning units. Based on guided and self-centred student learning the model is capable of recognising multiculturalism and diverse student learning needs. It supports and encourages contributions from all participants and a team approach to teaching and learning.